The Role Of Website In Improving Digital Marketing In E-Commerce MSME Macaroni Cheese: Peran Website Dalam Meningkatkan Digital Marketing Pada E-Commerce UMKM Makaroni Keju - Muhamad Azrino Gustalika; Dimas Fanny Hebrasianto; Annisaa Utami; Adithana Dharma Putra; Ervan Hapiz; Haposan Felix Marcel Siregar (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Icip-Icip Cheese Makaroni UMKM located in Wirasana Village, Purbalingga Regency. This UMKM focuses on making snacks, especially cheese makaroni with various flavors. Currently, Icip-Icip Cheese Makaroni products are only sold in Purbalingga Regency. One of the problems faced by Icip-Icip Cheese Makaroni UMKM is that marketing is not optimal, so many people do not know this product. Competition in the cheese makaroni industry is very fierce with other brands, so Icip-Icip Cheese Makaroni UMKM must develop a marketing strategy through digital marketing in order to compete and increase sales. This service resulted in 91.67% of UMKM satisfaction and the e-commerce application was successfully 100% run.